ANALISIS SISTEM INFORMASI AKUNTANSI UNTUK MENUNJANG PENGENDALIAN INTERNAL DALAM MENINGKATKAN LABA PERUSAHAAN (STUDI KASUS PADA LADYFAMESHOP BANDAR LAMPUNG) - Annisa Sokarisma Putri; Dhiona Ayu Nani; Vera Apri Dina Safitri; Annisa Sokarisma Putri (Journal Strategy of Management and Accounting Through Research and Technology (SMART), 2021)
AbstractAccounting information system is one of information systems that can be applied to support company activities, especially the sales accounting information system. This sales accounting information system is very important because it can support adequate   internal   control   over   sales.   With   adequate   internal   control, manipulation  of  sales  can  be  avoided.  This  is  what  makes  the  author  to  do research on Ladyfameshop Bandar Lampung. Ladyfameshop is a dress store that is engaged in sales, selling various kinds of clothing products for women and men. The purpose of this study is to determine the sales accounting information system to support internal control in increasing company profits at Ladyfameshop Bandar Lampung. This type of research is qualitative research. The data used are primary data. With data collection techniques, namely using observations, interviews, and documentation of parties related to the data needed in this study. The data analysis method used in this research is descriptive analysis. The results showed that the parts involved in sales at Ladyfameshop are customers, sales, accounting, stock list, warehouse, and shipping. The document used contains the name of the buyer and the number of items ordered, as well as for sales invoices (struck) there is already a printed serial number. The implementation of activities when implementing the sales accounting information system at Ladyfameshop is quite good and adequate. The organizational structure at Ladyfameshop fulfills internal controls, namely by having a clear job description of the duties and responsibilities of each personnel.